Design, technology, and poverty – Devices for the design of architecture, objects, and society - Alessandro Valenti; Francesca Scalisi; Cesare Sposito; Davide Fabio Colaci; Giacomo Moor (Agathón, 2025)
The paper analyses the contribution of Technological and Environmental Design and Architecture to overcoming poverty, one of the most urgent contemporary challenges, in line with Goal 1 of the UN Agenda 2030. Contextualising this issue in the global scenario, this paper critically illustrates some international events, research and good practices that are replicable and adaptable in similar contexts and are contributing to the cultural debate and action to eradicate poverty. It will be highlighted how the two disciplines can act in synergy as a pedagogical and economic tool, capable of promoting a culture of dignity and possibility for the design of architectures, objects, and societies, influencing, in a multidimensional way, the impact of poverty on people’s lives.